Penerapan Model Pembelajaran Project Based Learning Matematika Materi Kubus di SMP Negeri 3 Bolaang Kelas VIII - Sartika Dilapanga; Ichdar Domu; Rosiah J. Pulukadang (Journal on Education, 2024)
This research examined the average student mathematics learning outcomes when the Project Based Learning Model was applied in mathematics learning with Cube material. The research design used was Posttest Only Control Group Design. The population in this study was all class VIII at SMP Negeri 3 Bolaang. In contrast, the samples taken in this study were class VIII B, with 20 students as the experimental class and class VII A as the control class, with a total of 20 students. The analysis results from this research show that the average posttest score for the experimental class is 82.75, while the average posttest score for the control class is 73.25. The research results obtained were based on hypothesis testing using the T-test with a significance level of 5%. The value obtained was ????ℎ???????????????????? = 4.407 > ???????????????????????? = 1.68595, so reject ????0. So, it can be concluded that based on these results, the Project Based Learning model can improve student learning outcomes